Building the nation in Southern Sudan: state emblems, symbols and national identity - Ylönen, A. (Africa Review, 2020)
This article discusses a selection of state emblems, national symbols and national identity in Southern Sudan. The emblems and symbols are used to provide meaning to a nation in the making and serve as pillars for common national identification to guide the formation of national identity. In essence, they represent the top-down process of politically dominant societal actors’ attempt to effect nation building by seeking to promote their desired type of national identity. Drawing on field observations and analysis aimed at examining aspects of state symbols and national identity, the article shows that the meanings attached to the adopted state emblems and national symbols can be inclusionary or exclusionary and may encourage unity or division. It argues that any attempt to promote unifying and cohesive national identity following a long and divisive armed conflict, as in the case of Southern Sudan, requires the adoption of inclusive and positively meaningful state emblems and national symbols.